Analisis Manajemen Risiko dalam Pengambilan Keputusan Bisnis pada Perusahaan Startup - Yudi Pratama; Ilham Akbar; Farhan Ramdhan (Primary Journal of Multidisciplinary Research, 2026)
The rapid growth of startup companies in the digital era presents various opportunities as well as challenges, particularly in dealing with high business uncertainty. One of the key factors determining startup success is the ability to manage risk effectively. This study aims to analyze the implementation of risk management in business decision-making processes within startup companies, as well as to identify the most dominant types of risks they face. The research method employed is a qualitative approach, with data collection techniques including in-depth interviews, observations, and documentation studies conducted on several growing startups. The findings indicate that most startups encounter major risks such as financial risk, market risk, operational risk, and technological risk. The implementation of systematic risk management has proven to help companies identify, evaluate, and mitigate potential losses, thereby supporting more accurate and measurable decision-making. Furthermore, the study reveals that startups with adaptive and innovative organizational cultures tend to be more effective in managing risks. Therefore, risk management becomes a crucial element in enhancing the sustainability and competitiveness of startup companies amid dynamic and competitive market conditions. The implications of this study suggest that startup companies need to continuously integrate risk management into every strategic and operational process. In addition, support from stakeholders, the use of analytical technologies, and the improvement of human resource competencies in understanding risk are important factors in strengthening decision-making systems. This study is expected to provide practical contributions for startup business practitioners and serve as a reference for future research related to risk management and business decision-making.